KONFLIK BATIN TOKOH-TOKOH NOVEL “DENGAN HATI” KARYA SYAFRINA SIREGAR - Rusmala Dewi, Ni Made Ayu (Humanis, 2013)
This article analyzed the characters’ internal conflict in a novel, Dengan Hati (whith heart), written by Syafrina Siregar. This novel was interesting to be analyzed as it has a vivid psychology description in its main character who experienced an inner-self conflict. This novel describes fellowship, sacrifice, and suffering the loss of friends. The structure theory and the inner conflict theory were being used in this article. There are some motivations in writing this article; the main character’s fear when she is scared of being infected by HIV and describing the feeling of HIV patient who are discriminated when associating themselves with surrounding. By involving our inner sense, we can experience how they feel went down when they are being discriminated.
Keywords: Inner conflict, psychology